Turbulence in the Russian Economy Management System - Askerov, Pulat F.; Novichkov, Andrey V.; Novichkov, Victor I.; Nosova, Svetlana S.; Rabadanov, Ammakadi R. (International Journal of Economics and Financial Issues, 2016)
Topical events on economic and public arenas are eloquent of the beginning of a stage in manifestation of global market failures (fiasco) which cause increasing turbulence in the system of the economic development of advanced countries. The solution of this problem becomes particularly topical at that time when the globalization process, which is accompanied by world crises, rapidly grows and there is the need to make intelligent and educated decisions in a timely manner in the face of internal and external economy management change. Russia faces internal and geopolitical challenges and threats. External and internal factors, which cause the turbulent, namely, uncertain and chaotic development of the economy, have focused. As a fragment of the systemic way out of global turbulence can be considered the following: 1) on the basis of the fundamental classical economic theory it is necessary to reconstitute the reproduction chain, where production - distribution - exchange – consumption interact; 2) it is necessary to develop and implement a strategy of resource competitive advantages; 3) we offer to consider the import substitution as a new breakthrough to the growth in different industries where new chains of the rise in the cost of national welfare are developed. Keywords: Network economy, uncertainty, network effects, risk management, financial globalization, risks. JEL Classifications: E26, O10